Study of Synthesis and Spectroscopic Characterization of Some Water Soluble Zn(II) Complexes with Substituted N, N- donor Ligands Derived from Pyridine-2-Carbaldehyde - Kundu, Sajal; Singh, Keisham Surjit (New Innovations in Chemistry and Biochemistry Vol. 8, 2022)
This book chapter highlights synthesis and physio chemical characterization of a series of four reported zinc complexes with substituted N,N- donor ligands viz. Ln = (E)-N-(pyridin-2-ylmethylene) anilines with composition [Zn(NO3)2(L1)](1), [Zn(NO3)2L2] (2), [Zn(NO3)2L3] (3), [Zn(NO3)2L4] (4). The spectroscopic properties of the complexes were studied by UV-visible, fluorescence, IR and 1H NMR spectral analysis. All the complexes were water soluble and non-electrolyte in solution. Efforts for getting single crystals suitable for X-ray crystal structure to determine the geometry and structure of the complexes could not be achieved. However, on the basis of spectral studies and related Zinc(II) nitrate compounds reported earlier, all the complexes were predicted to be octahedral geometry (1-4) . The nitrate ion coordinated to zinc complexes through monodentate (1) or bidentate (2-4) fashion. The emission spectra of all the complexes showed \(π\)-\(π\)* (intra-ligand) transition and Zn compounds showed very low fluorescence quantum yield indicating that they were weak emitters at room temperature.